Genocide and resistance Nr. 48(2) - Indrišionis, Darius; Buchaveckas, Stanislovas; Burauskaitė, Teresė Birutė; Klumbys, Valdemaras; Rukšėnas, Alfredas; Pocius, Mindaugas; Vilkelytė, Daiva; Bartkutė, Roberta; Vitkus, Aleksandras (Genocidas ir rezistencija, 2020)
Full Issue